In vivo antifungal activities of farnesol combined with antifungal drugs against murine oral mucosal candidiasis. Issue 8 (14th September 2021) - Li, Chengxi; Xu, Zheng; Liu, Siqi; Huang, Yun; Duan, Wei; Wei, Xin
Abstract: The antifungal resistance of oral candidiasis is a serious clinical issue. The in vivo efficacy of farnesol combined with antifungals for oral candidiasis remains unknown. The possible therapeutic effects of a combination of farnesol and antifungal drugs and the regulation of inflammatory cytokines in murine oral candidiasis were investigated in this study. An experimental oral candidiasis model was constructed using ICR mice. Farnesol at 25 and 50 μM did not change IL-17, IFN-γ, and TNF-α production during oral candidiasis compared with that of the control infected mice. The co-applications of farnesol (50 μM) and nystatin, farnesol (4 μM, 8 μM) and itraconazole, farnesol (25, 50 μM), and fluconazole enhanced the therapeutic activity of the antifungal agents alone against oral candidiasis. The effective combinations reduced the number of colony- forming units (CFU) of Candida albicans isolated from the oral cavity and oral lesions on the tongue.